2016
DOI: 10.3389/fpsyg.2016.00891
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Day? A Guide to Decomposing the Variance in Intensive Longitudinal Data

Abstract: In recent years there has been a growing interest in the use of intensive longitudinal research designs to study within-person processes. Examples are studies that use experience sampling data and autoregressive modeling to investigate emotion dynamics and between-person differences therein. Such designs often involve multiple measurements per day and multiple days per person, and it is not clear how this nesting of the data should be accounted for: That is, should such data be considered as two-level data (wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…First, variance decomposition, using the intraclass correlation coefficient (ICC), was used to evaluate whether events or days were exchangeable within the individual. Following recommendations by de Haan-Rietdijk, Kuppens, and Hamaker (2016), variance decomposition models were conducted with an autoregressive 1 covariance matrix over events. For agreeable behavior, 91.29% of variance was explained at the event level, 1.94% at the day level, and 6.77% at the person level.…”
Section: Methodsmentioning
confidence: 99%
“…First, variance decomposition, using the intraclass correlation coefficient (ICC), was used to evaluate whether events or days were exchangeable within the individual. Following recommendations by de Haan-Rietdijk, Kuppens, and Hamaker (2016), variance decomposition models were conducted with an autoregressive 1 covariance matrix over events. For agreeable behavior, 91.29% of variance was explained at the event level, 1.94% at the day level, and 6.77% at the person level.…”
Section: Methodsmentioning
confidence: 99%
“…While some of these models have been used in dynamic mutlilevel analyses, allowing for individual differences in the dynamics parameters through modeling these as random effects at level 2 (see Asparouhov et al, 2017Asparouhov et al, , 2018Haan-Rietdijk, Gottman, Bergeman, & Hamaker, 2016;Wang et al 2012), this area is still largely unexplored. However, the need to move beyond firstorder autoregressive models is undeniable, whether the interest is in mere prediction or in actually understanding the underlying mechanism.…”
Section:  Alternative Modelsmentioning
confidence: 99%
“…Haan-Rietdijk, Kuppens, and Hamaker (2016) compared the two-level and three-level approach in the context of experience sampling data, where the two-level model consists of measures nested in persons, and the three-level model consists of beeps nested in days which are nested in persons. The results showed that autoregression in a two-level model may result from ignoring the three-level structure of the data.…”
Section:  Structural Missings Due To Nighttime or Weekendsmentioning
confidence: 99%
“…We focus on the N = 1 case where a model is fit to one person's data, using simulations as well as an empirical illustration to address the question of whether substantial bias in the parameters of interest may result from using DT (vector) autoregressive models. This is an important question because autoregressive (AR) models and extensions such as the vector autoregressive (VAR) model are frequently used in ESM research in areas such as affect dynamics (e.g., Suls et al, 1998 ; Koval and Kuppens, 2012 ; de Haan-Rietdijk et al, 2016 ; Van Roekel et al, 2016 ) and the emerging network approach to psychopathology (Borsboom and Cramer, 2013 ; Bringmann et al, 2013 ; Wichers, 2014 ). Thus, questions about the validity of DT model results for unequally spaced data bear directly on findings reported in these fields and on recommendations for follow-up studies, in addition to general questions about optimal design and data analysis for these types of studies.…”
Section: Introductionmentioning
confidence: 99%